Kesalahan Berbahasa Tataran Sintaksis pada Berita Surat Kabar Tribun Pekanbaru - Desy Agustina; Alber (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The analysis of language error is work procedure commonly used by researchers or teachers, which includes: Activity collects error sample, identifying errors contained in the sample, explaining the error, classfying the error, and evaluatingthe fairest of the error. The error of speaking is still found in the newspaper Tribun Pekanbaru. The matter of this research is how the syntax tissue error is the phrase on the news of the newspaper Tribun Pekanbaru?. The theory used is the theory that is set Setyawati (2010) and some expert supporting theories. The method used is documentation and hemeneuretic techniques. Research resultAnalysis of Syntaxis Tarant Effects on News Tribun Pekanbaru there is an effect of the language of the area there are 3 data, the use of omproper prepositions there are 1 data, the improper arrangement of there are 1 data, the use of excessive or maxzzle venues there are 7 data, the use excessive superlative forms there is 1 data, double checkbook there are 1 data, and the use of wrong resiprocal form there is 1 data.